An open-source simulation platform to support and foster research collaboration in natural hazards engineering - Zsarnóczay, Adam; Deierlein, Gregory G.; McKenna, Frank; Schoettler, Matthew; Yi, Sang-Ri; Cetiner, Barbaros; Satish, Aakash Bangalore; Zhao, Jinyan; Bonus, Justin; Melaku, Abiy F.; Naeimi, Sina; Arduino, Pedro; et al. (Frontiers in Built Environment, 2025)
Computational simulation is a critical tool for assessing the impacts of natural hazards and informing risk mitigation and resilience strategies. The NHERI SimCenter has developed an open-source, modular framework that integrates performance-based engineering methodologies with regional-scale assessments to enable multi-hazard, multi-scale simulations. This paper presents the conceptual foundation and current capabilities of the SimCenter platform, covering hazard characterization, structural response analysis, damage and loss estimation, and recovery modeling. By leveraging high-performance computing, standardized data schemas, and open-source tools, the platform facilitates transparent, reproducible research while bridging local and regional analyses. Key contributions include improved inventory generation, damage simulation, and recovery analysis, with applications extending across multiple hazard domains. The paper also discusses challenges in implementing high-resolution, high-fidelity simulations, advancing multi-hazard assessments, and enhancing accessibility for a broad user base. Looking ahead, expanding hazard models, refining regional-to-local modeling techniques, and fostering community collaboration will be essential for advancing computational simulation in natural hazards engineering. Through continued development, the SimCenter aims to provide researchers and practitioners with scalable, adaptable tools to enhance disaster risk assessment and resilience planning.